Case report: Approaches to treatment-refractory and super-refractory glutamic acid decarboxylase antibody-spectrum disorders - Rajmohan, Ravi; Baveja, Shivali; Nguyen, Dai; Shah, Eshita; Sy, Michael; Attaripour, Sanaz; Swope, David (Frontiers in Immunology, 2024)
Background Glutamic acid decarboxylase antibody-spectrum disorders (GAD-SDs) include a group of autoimmune neurological diseases associated with neuronal excitability, most noticeably stiff person syndrome. Immune modulators are the mainstay of treatment, but a significant number of patients remain refractory. Methods We present our single-center experience of eight cases of GAD-SD, two of which were refractory to immune modulatory treatments. Results Of the two cases that were refractory to immunomodulation, one showed significant improvement with bilateral globus pallidus interna deep brain stimulation (GPi DBS) placement, and the other showed significant improvement with autologous hematopoietic stem cell transplant (aHSCT). Discussion To our knowledge, this is the first instance of GPi DBS placement being noted to improve GAD-SD movements.